2014
DOI: 10.14430/arctic4382
|View full text |Cite
|
Sign up to set email alerts
|

Linking Wolf Diet to Changes in Marine and Terrestrial Prey Abundance

Abstract: ABSTRACT. Since most wolf (Canis lupus) diet studies have been conducted in inland ecosystems, comparatively few data are available on diets of wolves in coastal systems. We investigated the diet of wolves in Glacier Bay, Alaska, from 12 May to 28 June in both 2010 and 2011. Although we identified 12 different prey species, including birds and small to medium-sized mammals, in wolf scats, moose (Alces alces) was the most frequent food item, observed in 80% of all scats. In contrast, a study conducted in 1993 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…), black bears ( Ursus americanus ), seals ( Phoca spp. ), and birds and small mammals (Smith et al 1987, Kohira and Rexstad 1997, Szepanski et al 1999, Lafferty et al 2014). However, the biogeographic variation in wolf diets has not been studied in this region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), black bears ( Ursus americanus ), seals ( Phoca spp. ), and birds and small mammals (Smith et al 1987, Kohira and Rexstad 1997, Szepanski et al 1999, Lafferty et al 2014). However, the biogeographic variation in wolf diets has not been studied in this region.…”
Section: Introductionmentioning
confidence: 99%
“…A key assumption of these models was that carrying capacity of Sitka black‐tailed deer will largely drive population abundance of wolves, a reasonable premise considering that deer were found to be the key prey item of wolves on POW (Kohira and Rexstad 1997). However, this assumption might not be valid at the regional scale (Southeast Alaska) given evidence of prey switching when ungulate abundance shifts (Lafferty et al 2014), reliance on alternate prey in geographical regions where deer abundance is relatively lower (Szepanski et al 1999), and seasonal use of specific prey items (e.g., salmon; Szepanski et al 1999, Darimont and Reimchen 2002). Therefore, it is necessary to expand the breadth of knowledge about wolf diets in other areas of this heterogeneous environment because geographical and biological differences between islands and coastal mainland systems influence ungulate occurrence and abundance, and these differences could be reflected in wolf diets (Darimont et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Maximizing encounters and detection of prey by selecting areas of high prey density increases the likelihood of a successful predation event (Hopcraft et al 2005;Bergman et al 2006). Wolves Canis lupus are opportunistic predators (Becker et al 2008) and tend to select the most abundant prey (i.e., highest biomass; Kunkel and Pletscher 2001;Smith et al 2004; but see research on coastal wolves by Darimont et al 2008;Adams et al 2010;Lafferty et al 2014), although research also suggests wolf prey selection is further influenced by prey vulnerability (Bergman et al 2006;Mattioli et al 2011). Wild ungulates comprise the majority of the diet of wolves (Mattioli et al 1995;Gazzola et al 2007;Imbert et al 2016), and unsurprisingly, wolves also favor areas of high ungulate density (Hebblewhite and Pletscher 2002;Garrott et al 2005;Alexander et al 2006;Bergman et al 2006), particularly in winter (Fritts and Mech 1981;Forbes and Theberge 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent diet studies of both felid and canid species depended solely on field identification of scats (Braczkowski et al , Kozlowski et al , Mondal et al , Lafferty et al , Etheredge et al , Kerley et al ). Although previous studies have identified high error rates in field identification of scats (Anwar et al , Shehzad et al , Jumabay‐Uulu et al , Kachel ), the potential discrepancy between heuristic and molecular food‐habits analyses has yet to be evaluated.…”
mentioning
confidence: 99%